The Spanish Version of the International Index of Erectile Function: Adaptation and Validation - Díaz-Mohedo, Esther; Meldaña Sánchez, Antonio; Cabello Santamaría, Francisco; Molina García, Elena; Hernández Hernández, Sofía; Hita-Contreras, Fidel (IOAP-MDPI, 2023)
Background: The International Index of Erectile Function (IIEF) is a widely employed questionnaire in urology to assess erectile dysfunction (ED) in both clinical research and practice. Objective: To translate and culturally adapt the Spanish version of the International Index of Erectile Function (IIEF) and to analyze its psychometric properties in Spanish men with erectile dysfunction (ED). Methods: Firstly, direct and reverse translations were performed. Secondly, a pilot study was carried out on 23 patients with the lowest possible education level without being illiterate. Finally, 170 participants completed the IIEF. Test–retest reliability, internal consistency and construct validity (exploratory factor analysis) were assessed. Concurrent and divergent validity were evaluated with the Hospital Anxiety and Depression Scale (HADS) and the 12-item Short-Form Health Survey (SF-12), respectively. Discriminant validity (with and without anxiety or depression) was calculated using a receiver-operating characteristic curve analysis. Results: High internal consistency (Cronbach’s alpha = 0.968, total score) and moderate-to-excellent test–retest reliability were found. The factor analysis showed a two-factor structure (explained variance of 77.34%). Significant correlations of the IIEF total score (p < 0.01) and domains (p < 0.05) with HADS anxiety and depression scores were observed (concurrent validity), while non-significant correlations with SF-12 physical and mental summary scores were found (divergent validity). The IIEF total score could discriminate between participants with and without anxiety (p < 0.05) and depression (p < 0.01), with an optimal cut-off point of <39.50 for both anxiety (48.30% sensitivity and 78.75% specificity) and depression (50.00% sensitivity and 81.01% specificity). C. (...)
Keywords: Psicometría; Erectile function; Spanish; Validation; Psychometric